On the differential diagnostic prospects of determining the profile of the lateral organization of the personality during assessment of the systematic alcohol abuse - K. A. Bamburov; Z. V. Lukovtseva (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The article is devoted to the question of the possible improvement of the psychological examination of persons previously examined in alcoholic intoxication (hereinafter—PEAI). The authors propose an original view on the definition of the target of «alcohol screening», the principles and methods of assessing psychological markers of the systematic substance abuse. Purpose of the study: to determine the differential diagnostic significance of identifying the profile of the lateral organization (hereinafter—PLO) when assessing of the systematic of alcohol abuse in those previously examined in a state of alcoholic intoxication. The researchers made an attempt to highlight the features of PLO of such a «risk group» as those previously examined in a state of alcoholic intoxication (based on data obtained during the study according to the typology of E.D. Khomskaya (with a combination of three types of asymmetries: manual, auditory-verbal and visual) of lateral preferences of 19 PEAI patients of the branch of the Moscow Research and Practical Center for Narcology). As a result, the tendency of those previously examined in the state of intoxication to the lack of a «leading ear» and «leading eye», significant differences in the distribution of the attribute «leading hand» among those previously examined in a state of alcoholic intoxication and in the population were revealed. Conclusion. According to the results of this study, it is difficult to assume the presence of a significant differential diagnostic significance of PLO detection during «alcohol screening» among those previously examined in a state of alcoholic intoxication. At the same time, it should be noted that taking into account lateral preferences can contribute to the improvement of preventive work programs in the narcological service, providing greater individualization of psychological support measures. Directly in the rehabilitation work with PEAI, it is advisable to actively apply social and psychological training (because of a significant part of the contingent among the main factors of relapse with a high degree of probability has social stressors). The creation of short-term (3-5 meetings) programs of group exercises of a preventive orientation, which have different targets depending on the «vulnerability factors» of the owners of certain lateral profiles, also seems justified.